Competitive conditions in the Jamaican banking market 1998 - 2009 - Jenifer Daley; Kent Matthews (Cardiff University, Cardiff Business School, 2011)
This paper presents an empirical assessment of the degree of competition within the Jamaican banking sector during the period 1998 to 2009. We employ a dynamic version of the Panzar-Rosse Model to estimate market power among the sample of banks that constitute over 90 percent of the banking market. Using the conventional statistical tests, we are unable to reject monopoly/perfect collusion for the merchant banking sector in Jamaica but find competitive conditions in the commercial banking sector. This contrasts with earlier findings using alternative estimators that find monopolistic competition in the market as a whole.
Keywords: G21; G28; 330; competition; banking; Rosse-Panzar H statistic; dynamic panel estimation; Jamaica